Knowledge of home blood pressure monitoring among medical students in Malaysia - Ching, Siew Mooi; Soo, Man Jun; Chong, Shen Horng; Devaraj, Navin Kumar; Ng, Jun Ying; Leong, Yong Jian; Lee, Kai Wei; Patil, Mansi; Lim, Hooi Min; Beh, Hooi Chin; Suppiah, Subapriya; Yusof Khan, Abdul Hanif Khan (Universiti Putra Malaysia, 2023)
Introduction: As future healthcare providers, it is vital for medical students to be well-versed in home blood pressure monitoring (HBPM), which plays a crucial role in hypertension management. This study aimed to assess the level of knowledge on HBPM among medical students and factors associated with good knowledge. Method: A cross-sectional study was conducted among Year One to Five medical students in a Malaysian public university using universal sampling. Data was gathered via an online questionnaire on HBPM knowledge. The analysis of the data was performed using SPSS v26. Multiple logistic regression identified the determinants of good HBPM knowledge after adjusting for confounding. Results: A total of 370 medical students were recruited. The median age was 22 (2) years old, and 73.2% were female. 63.2% of them were from clinical years. The proportion of medical students with good HBPM knowledge was 55.7% (28.7% from preclinical students and 46% from clinical-year students). Multiple logistic regression revealed that clinical-year students were more likely to have good knowledge about HBPM than preclinical-year students. (OR=2.96; 95% CI=1.91-4.58, p<0.001). Conclusion: This study showed that preclinical-year students possess a poorer knowledge of HBPM. However, less than half of clinical year students exhibited good knowledge, despite greater patient exposure suggesting current clinical teaching may not impart comprehensive HBPM understanding. Medical schools should strengthen the curriculum by incorporating more practical HBPM learning during clerkships and rotations. This can better equip future physicians to effectively utilize HBPM for diagnosing and managing hypertension.